UPAYA MAJELIS TA’LIM Al-ISLAMY DALAM MELESTARIKAN NILAI-NILAI ASWAJA - Bagus Walasasmita; Fathurrahman Alfa; Yorita Febry Lismanda (VICRATINA, 2020)
Islam is a perfect and universal religion, a religion that make all aspects of human life. Islam is a system of life that no system can match and like, because all of these systems are God's creation. Therefore, humans are equipped with a mind to formulate a system that can be used as a tool or a way to explain the understanding of Islam. Basically the Islamic concept of education, aims to maintain human nature, bequeath the values, and the formation of a whole human being (insan kamil) based on the Qur'an and the Hadith of the Prophet SAW.The lecture method is a way of conveying information through verbal explanation and information by the teacher to students (Afifulloh, 2019)The role of the majelis ta’lim in preserving the Aswaja values ,namely as a forum for fostering and developing religious life in order to form a community that is devoted to God.Spiritual recreation park, because its implementation is relaxed.Media for delivering ideas that are benefit to the development of people and nation.The Al-Islamy ta'lim assembly in an effort to preserve Asawaja's values is by following the teachings of the ulama 'salaf, while in the learning method in the ta’lim assemblyAl-Islamy does not have a curriculum like public schools, but it does activities in the majelis ta’lim are structured.